2007
DOI: 10.1242/jeb.004671
|View full text |Cite
|
Sign up to set email alerts
|

The hungry caterpillar: an analysis of how carbohydrates stimulate feeding inManduca sexta

Abstract: SUMMARY In most insects, the taste of carbohydrates stimulates an immediate appetitive response. The caterpillar of Manduca sexta is an exception to this general pattern. Despite eliciting a strong peripheral gustatory response, high concentrations of carbohydrates (e.g. glucose or inositol)stimulate the same intensity of biting as water during 2-min tests. We suspected that the lack of feeding stimulation reflected the fact that prior studies used single carbohydrates (e.g. sucrose), which M. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 76 publications
(91 reference statements)
1
23
0
Order By: Relevance
“…An important factor which stimulates larvae to feed is the abundance of nutrients in leaves (Bede et al 2007). Insects more willingly select leaves that are rich in amino acids and carbohydrates (Glendinning et al 2007). The level of amino acids in the leaves may be an important factor affecting the size of the phytophagous population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important factor which stimulates larvae to feed is the abundance of nutrients in leaves (Bede et al 2007). Insects more willingly select leaves that are rich in amino acids and carbohydrates (Glendinning et al 2007). The level of amino acids in the leaves may be an important factor affecting the size of the phytophagous population.…”
Section: Discussionmentioning
confidence: 99%
“…Plant amino acids are a key source of nitrogen, which is a significant factor in egg production (Cahenzli and Erhardt 2013). Carbohydrates, which are also an important component in the diet of many Lepidoptera, cover energy requirements and provide carbon skeletons for somatic development, fitness and reproductive output (Glendinning et al 2007;Marchioro and Foerster 2013). High activity of amylase, maltase and saccharase which was found in the midgut of C. ohridella suggests that starch, maltose and saccharose are primary carbohydrate components of their diet (Stygar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first second of the discharges was selected as representative of the phasic/phasictonic portion of the response (Glendinning et al 2001(Glendinning et al , 2007; our data were reported as mean values of spike firing frequency ± standard error of the mean (S.E.M.). Spike sorting and counting were performed by means of Clampfit 10.0 software (Axon Instruments Inc, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that postingestive effects, acting independently of taste quality, function as physiological reinforcers, ultimately leading to increased sugar intake (Sclafani, 2001;Glendinning et al, 2007). Here we tested the hypothesis that D-glucose will be consumed at higher levels compared with a free L-amino acid even when gustatory influence is eliminated and that such an effect is associated with nutrient-specific responses in brain dopamine systems.…”
Section: Introductionmentioning
confidence: 99%